Reservoir characteristics and pore fluid evaluation of Shan 23 Submember transitional shale, eastern Ordos Basin, China: Insights from NMR experiments - Cai, Guangyin; Gu, Yifan; Xiong, Xianyue; Li, Xingtao; Sun, Xiongwei; Ni, Jia; Jiang, Yuqiang; Fu, Yonghong; Ou, Fang (Frontiers in Earth Science, 2023)
The Lower Permian Shanxi Formation in the Eastern Ordos Basin is a set of transitional shale, and it is also a key target for shale gas exploration in China. Three sets of organic-rich transitional shale intervals (Lower shale, Middle shale and Upper shale) developed in Shan 23 Submember of Shanxi Formation. The brittleness index of the Middle shale is the highest, reflecting the relatively strong ability of fracturing. While the Upper shale is characterized by weak ability of fracturing. The total gas content of the Middle and Lower shale is high, and the content of lost gas and desorbed gas accounts for 80% of the total gas content, reflecting the high reservoir quality. Based on a series of NMR experiments, it is suggested that the Middle shale has the highest movable water content and the lowest capillary bound water content. The Lower shale has the highest capillary bound water content, but the movable water content is low. The Middle shale and the Lower shale have high movable pores, and the proportion can reach 27%. The total content of movable pores and bound pores in the Lower shale is the highest, while that in the Upper shale is lower. It is suggested that the Lower and Middle shales have more development potential under the associated development technology.